Mary Parker Follett, managerial responsibility, and the future of capitalism. (April 2015) - Berman, Shawn L.; Van Buren, Harry J.
Highlights: Contemporary employment practices have reduced worker attachment to organizations. Reduced worker attachment and perceived unfairness threatens capitalism's support. Mary Parker Follett's insights about management are have contemporary relevance. Her insights about integration and participation in organizations merit attention. More integration and participation would help assure a just future for capitalism. Abstract: In this paper we examine the work of Mary Parker Follett as it relates to current management practice. Specifically, we focus on her development of the concepts of integration and participation with respect to the employer–employee relationship in the context of the low-skill workforce. At their core, both of these concepts relate to the idea that management should attend to the concerns of workers. However, recent trends that have had the effect of reducing the attachment of workers to their organizations, particularly changes in the psychological employment contract and the use of contingent and temporary workforces, also reduce the likelihood of genuine integration and participation in organizations. We then connect these changes to the problem of income inequality and suggest that the same organizational practices that have reduced employee attachment may also lead many people to question the legitimacy of capitalism as an economic system through the absence of a societally shared prosperity. We suggest that by reconnecting to Follett's concepts of integration and participation in the employer–employee relationship, better results can be obtained for both organizations and workers, leading to restored faith in capitalism. We close with an agenda for future research based on the implications of Follett's work for present-day organizations and society.